High-frequency operation of a DC/AC/DC system for HVDC applications - Lueth,T; Merlin,MMC; Green,TC; Hassan,F; Barker,CD (IEEE Transactions on Power Electronics, 2014)
Voltage ratings for HVdc point-to-point connections are not standardized and tend to depend on the latest available cable technology. DC/DC conversion at HV is required for interconnection of such HVdc schemes as well as to interface dc wind farms. Modular multilevel voltage source converters (VSCs), such as the modular multilevel converter (MMC) or the alternate arm converter (AAC), have been shown to incur significantly lower switching losses than previous two- or three-level VSCs. This paper presents a dc/ac/dc system using a transformer coupling two modular multilevel VSCs. In such a system, the capacitors occupy a large fraction of the volume of the cells but a significant reduction in volume can be achieved by raising the ac frequency. Using high frequency can also bring benefits to other passive components such as the transformer but also results in higher switching losses due to the higher number of waveform steps per second. This leads to a tradeoff between volume and losses which has been explored in this study and verified by simulation results with a transistor level model of 30-MW case study. The outcome of the study shows that a frequency of 350 Hz provides a significant improvement in volume but also a penalty in losses compared to 50 Hz.